215k views
4 votes
-5 ( 4 x + -5 ) = 5 x

2 Answers

5 votes

Let's solve your equation step-by-step.

−5(4x−5)=5x

Step 1: Simplify both sides of the equation.

−5(4x−5)=5x

(−5)(4x)+(−5)(−5)=5x(Distribute)

−20x+25=5x

Step 2: Subtract 5x from both sides.

−20x+25−5x=5x−5x

−25x+25=0

Step 3: Subtract 25 from both sides.

−25x+25−25=0−25

−25x=−25

Step 4: Divide both sides by -25.

-25x/-25=-25/-25

Therefore, the answer is x=1.

User Noontz
by
5.2k points
2 votes
x=1. Hope this helps!!! :)
-5 ( 4 x + -5 ) = 5 x-example-1
User Cereal
by
4.9k points